Anti-phosphorylcholine response of autoimmune NZB/W mice: variations with age of serum titers and homogeneity (Revista Española de Fisiología, 1987)
Antibody titers and avidity of sera of autoimmune NZB/W mice in responses induced by different antigens were determined.Results show an age-dependent decrease of the antibody titer in sera from female mice immunized with phosphorylcholine coupled to keyhole limpet haemocyanin.This decrease was not detected when using as immunogen an antigenic preparation of Neisseria meningitidis that naturally induces anti-phosphorylcholine antibodies, but was detected with a modification of this antigen (heat inactivation and further coupling with the hapten).Determinations of inhibition profiles of antisera suggest that this loss of immune competence is paralleled by a decrease in avidity and homogeneity of antisera.This finding may be related to the loss of idiotypic clonal dominance recently reported to occur in these mice.